2007
DOI: 10.4102/sajip.v33i2.372
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric evaluation of measures of effective well-being in an insurance company

Abstract: The objectives of this study were to validate two measures of affective well-being, namely the Maslach Burnout Inventory (MBI) and the Utrecht Work Engagement Scale (UWES) for employees in an insurance company, to assess their construct equivalence for different language groups and to determine the relationship between burnout and work engagement. A cross-sectional survey design with an availability sample (N = 613) was used. The MBI, UWES and a biographical questionnaire were administered. Structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
(32 reference statements)
2
13
0
Order By: Relevance
“…The insurance industry is highly competitive and rivalry between organisations is fierce (Chan 2002), which leads to decreased employee wellbeing, stress and ill-health (Coetzer & Rothmann 2007). The United States and other countries have indicated that there is expected to be a shortage of skilled insurance professionals in coming years, owing to the retirement of workers, with a potential talent gap (Cole & McCullough 2012).…”
Section: The Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The insurance industry is highly competitive and rivalry between organisations is fierce (Chan 2002), which leads to decreased employee wellbeing, stress and ill-health (Coetzer & Rothmann 2007). The United States and other countries have indicated that there is expected to be a shortage of skilled insurance professionals in coming years, owing to the retirement of workers, with a potential talent gap (Cole & McCullough 2012).…”
Section: The Contextmentioning
confidence: 99%
“…The UWES measures three components of work engagement, namely vigour ("At my job I feel strong and vigorous"), dedication ("At my work I always persevere, even when things do not go well"), absorption ("I am immersed in my work"), on a seven-point Likert scale ranging from 1 ("Never") to 7 ("Always"). The UWES has been used extensively in the South African context and produced acceptable levels of internal consistency ranging from 0.65 to 0.96 on the various subscales (Coetzer & Rothmann 2007;Field & Buitendach 2011).…”
Section: Measuring Instrumentsmentioning
confidence: 99%
“…Coetzer & Rothmann, 2007;Mills, Culbertson & Fullagar, 2011;Nerstad, Richardsen & Martinussen, 2010;Salanova, Agut & Peiro, 2005;Seppälä et al, 2009;Storm & Rothmann, 2003), and also for other versions of the scale (e.g. Balducci et al, 2010;Fong & Ng, 2011;Hallberg & Schaufeli, 2006;Xanthopoulou, Bakker, Kantas & Demerouti, 2012;Yi-Wen & Yi-Qun, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They referred to the relatedness between posttraumatic stress and post-traumatic growth. Other examples of this relatedness of positive and negative are found in the research on engagement and burnout (Coetzer & Rothmann, 2007; Van der Colff & Rothmann, 2009), hope and despair, love and hate (Snyder & Lopez, 2002). Although our analysis of the nature of Positive Psychology gave evidence of constructs that are studied in their positive-negative relatedness, in general there seems to be a denial of the negative which may create an illusion amongst academics, students and organisational consultants about what positive psychology is really about.…”
Section: What Happens With the Negative In Positive Psychology?mentioning
confidence: 93%